Análisis de los créditos menores de 1000.00 dólares de la Cooperativa de Ahorro y Crédito Alli Tarpuc y su impacto en el desarrollo socioeconómico en la ciudad de Riobamba en el periodo 2013. - Arias Moncayo, María Fernanda (2016)
This research project concerns the analysis of minors credits 1000.00 dollars from the credit union Alli Tarpuc in the city of Riobamba in the 2013 period; Regarding the impact on socioeconomic development. Microcredit helps partners achieve financial develop their commercial activities thus achieve the desired home economics why this type of loan helps the economic development within the city of Riobamba is given institution. This research work is constituted by five chapters, they developed the same as follows: Chapter I, in this chapter the reference framework is developed, which includes the planning and formulation of the problem, objectives and rationale of why and wherefore of this investigation. Unit I data consisting of the credit union Alli Tarpuc: Chapter II, Theoretical Framework, it is divided into three units is detailed. Unit II covers and comprises everything related to microcredit. Unit III refers to socioeconomic development. Chapter III, the methods used for research, population and sample, operationalization of variables, techniques and tools for data collection, processing, analysis and interpretation of results and hypothesis testing are detailed. Chapter IV, conclusions and recommendations are made to establish the analysis of the results of the issues raised at the beginning of the investigation. The bibliography and the respective research is also attached.